A Policy Analysis Regarding Education, Career, and Governance of the Nurses in Bangladesh: A Qualitative Exploration. (May 2021) - Joarder, Taufique; Parvage, Md. Aslam; Rawal, Lal B.; Ahmed, Syed Masud
Nurses, short in production and inequitable in the distribution in Bangladesh, require the government's efforts to increase enrolment in nursing education and a smooth career progression. Given the importance of an assessment of the current nursing scenario to inform the decision makers and practitioners to implement the new policies successfully, we analyzed relevant policies on education, career, and governance of nurses in Bangladesh. We used documents review and qualitative methods such as key informant interviews ( n  = 13) and stakeholder analysis. We found that nursing education faced several backlashes: resistance from diploma nurses while attempting to establish a graduate (bachelor) course in 1977, and the reluctance of politicians and entrepreneurs to establish nursing institutions. Many challenges with the implementation of nursing policies are attributable to social, cultural, religious, and historical factors. For example, Hindus considered touching the bodily excretions as the task of the lower castes, while Muslims considered women touching the body of the men immoral. Nurses also face governance challenges linked with their performance and reward. For example, nurses have little voice over the decisions related to their profession, and they are not allowed to perform clinical duties unsupervised. To improve the situation, the government has made new policies, including upliftment of nurses' position in public service, the creation of an independent Directorate General, and improvement of nursing education and service. New policies often come with new apprehensions. Therefore, nurses should be included in the policy processes, and their capacity should be developed in nursing leadership and health system governance.